Elliptic flow from thermal photons with magnetic field in holography - Mueller, Berndt; Wu, Shang-Yu; Yang, Di-Lun (My University, 2014)
We compute the elliptic flow v(2) of thermal photons in a strongly coupled plasma with constant magnetic field via gauge/gravity duality. The D3/D7 embedding is applied to generate the contributions from massive quarks. By considering the cases in 2 + 1 flavor super Yang-Mills analogous to the photon production in quark gluon plasma, we obtain the thermal photon v(2), which is qualitatively consistent with the direct photon v(2) measured at the relativistic heavy ion collider at intermediate energy. However, due to the simplified setup, the thermal photon v(2) in our model should be regarded as the upper bound for the v(2) generated by solely a magnetic field in the strongly coupled scenario.